Peningkatan Prestasi Belajar Bahasa Inggris melalui Metode Mind Mapping di MAN I Gunungkidul - Surini Surini (Jurnal Pendidikan Madrasah, 2018)
This research discusses the implementation of giving task by using Mind Mapping method. Using Mind Mapping method is hoped that it can help the students to understand and to improve the students’creativity. This research is taken to 20 students of XII Science 3 of MAN 1 Gunungkidul. The teacher watches the students’activity and their team work. This research can be said success after the students get the score > 7.00. it gets >80% and it means that it reaches improvement in the students’activity. The method that is used in this research is Class Action Research. This research run in two cyles. Every cycle uses the procedures of planning, doing, observation and reflection. From the result in the first cycle, the students can get > 7.00 that is 54,54% with the creativity level is average. Based on the first cycle, it is continued to the second cycle. In the second cycle, the students get the mark > 7.00, it gets 81.81 % with the activity level is high. It is matched with the hope that this research can optimalize the students’ ability in mastering the english vocabulary in the second cycle. Based on the research it can be concluded that the method of Mind Mapping can make the students ability in mastering english vocabulary optimal. It can improve the efectivity of the students’ English learning.